Penerapan Konsep Desain Interior dan Dynamic Lighting Untuk Terapi Circadian Rhythm Sleep Disorders - Andriano Simarmata; Abel Alvieto (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Sleep disorders are a prevalent issue with significant implications for human well-being. This research focuses on studying interior design concept and dynamic lighting tailored for individuals with sleep disorders aiming to create a supportive environment through human circadian rhythm. Through literature analysis and experiment-based methods, key design factors including lighting and human circadian rhythm system were identified. The outcome is a comprehensive interior design concept for theraputic purpose that promotes comfortable sleep and relaxation by synchronizing lighting design responding to the behavioural changes following 24-hour cycle. This study also explores timed interior lighting scenario for effective sleep therapy processes, aiming to enhance the quality of life for individuals with sleep disorders.